Clinical Significance and Characterization of AZT-Resistant Strains of HIV-1 - Mark A Wainberg; Ronald Rooke; Michel Tremblay; XuGuang Li; Michael A Parniak; Qing Gao; Xiao-Jian Yao; Chris Tsoukas; JSG Montaner; M Fanning; J Ruedy (Canadian Journal of Infectious Diseases)
A number of laboratories have now independently confirmed that zidovudine (AZT)-resistant strains of human immunodeficiency virus type 1 (HIV-1) may be isolated from patients undergoing prolonged therapy with this drug. In certain instances, such drug-resistant viral isolates have been obtained from patients with clinical acquired immune deficiency syndrome (AIDS), while in others, isolation of drug-resistant strains has been achieved in the case of HIV seropositive, asymptomatic subjects. Most of the evidence points to a series of mutations within the polymerase gene of HIV-1, which encodes viral reverse transcriptase, as being responsible for development of the drug-resistant phenotype. It further appears that over 50% of patients treated with AZT for periods longer than six months are likely to yield drug-resistant strains of HIV-1 in their circulation. Furthermore, the development of drug resistance soon after initiation of AZT therapy may potentially be correlated with the likelihood of AZT treatment failure. In several instances, cross resistance has been observed between AZT and other nucleosides being considered for potential therapy of HIV-1-associated disease.